SOCIO ECONOMIC EMPOWERMENT IN AREA PRONE TO FLOOD (Flood Case Study in Periuk District, Tangerang City): PEMBERDAYAAN SOSIAL EKONOMI MASYARAKAT DI DAERAH RAWAN BANJIR (Studi Kasus Banjir di Kecamatan Periuk Kota Tangerang) - Baghas Budi Wicaksono Budi; FX. Pudjo Wibowo; Agus Kusnawan; Eso Hernawan (Adi Widya : Jurnal Pengabdian Masyarakat, 2023)
Empowerment of the environment in society is very essential in the regional and national development agenda. Communities, governments, academics and business actors have an important role as drivers of innovation in national environmental preservation programs. In an effort to implement this function, several strategic studies are needed so that all initiator components can jointly protect the environment from potential natural releases including natural disasters such as floods. Based on this, community service research involving members of the Tangerang City DPRD, the Environment Service, the Public Works and Public Housing Service, the Social Service, the Regional Disaster Management Agency, Officials in the Periuk sub-district and Periuk Sub-District underwent a Focus Group Discussion on social impact economic consequences due to flooding in Periuk District. As for some assistance with problems, namely as follows: 1.) Officials in the Tangerang City area require intensive coordination and supervision to overcome flood problems and their economic impacts, (2.) The need for knowledge for the community regarding the socio-economic impacts that can be experienced as a result of flooding . Therefore, the results of community service research are as follows: (1) succeeded in formulating a policy package that has been approved by the executive and legislative components in the Periuk District and Tangerang City, (2.) The community feels helped by the existence of discussion and presentation facilities material organized by the Business Faculty of Buddhi Dharma University.